Improving students' pronunciation through accent reduction software - Seferolu, Glge (British journal of educational technology, 2005)
This study aimed to find out whether integrating accent reduction software in advanced English language classes at the university level would result in improvements in students’ pronunciation at the segmental and sup‐rasegmental levels. The study made use of a quasi‐experimental research design. Two classes at the Department of Foreign Language Education at Middle East Technical University in Turkey participated in the study. Whilst one class (the control group) followed traditional instruction, the other class (experimental group) followed instruction which integrated use of accent reduction software in a multimedia language laboratory. Based on the results of the study, it is suggested that especially in English as a Foreign Language (EFL) settings where natural target language input is scarce, technology has a lot to offer, and EFL learners may be provided with exposure and practice/interaction opportunities in the target language through specifically designed software programs.